2023
DOI: 10.30574/gscbps.2023.22.3.0127
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profiling of Wistar rats fed with processed breadfruit

Abstract: Background: Breadfruit is a staple leguminous food that is widely consumed in the tropical and subtropical regions of the world and is an important source of dietary nutrients for adults, infants and children. Aim: This study is aimed at identifying the effect of feed fortification with processed breadfruit on the bodyweight and Lipid profile of Wistar rats. Methods: The Lipid profile was determined using standard diagnostic methods. Results: The results gotten from the research showed a continuous increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been reported that circulatory erythrocytes and diagnosis of anemia are evaluated by some major indices such as packed cell volume, hemoglobin, and mean corpuscular hemoglobin [16]. Also, earlier studies revealed that processing of breadfruit does not have a detrimental effect on the lipid profile parameters of wistar rats which shows that breadfruit consumption can be encouraged [17]. The packed cell volume concentration of the fortified rats showed a nonsignificant increase (p>0.05) when compared to the normal control with the exception of groups fortified with 30% and 50% of grilled breadfruit.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that circulatory erythrocytes and diagnosis of anemia are evaluated by some major indices such as packed cell volume, hemoglobin, and mean corpuscular hemoglobin [16]. Also, earlier studies revealed that processing of breadfruit does not have a detrimental effect on the lipid profile parameters of wistar rats which shows that breadfruit consumption can be encouraged [17]. The packed cell volume concentration of the fortified rats showed a nonsignificant increase (p>0.05) when compared to the normal control with the exception of groups fortified with 30% and 50% of grilled breadfruit.…”
Section: Discussionmentioning
confidence: 99%